Antibacterial Activity Test of Wet and Dried Extracts of Calabash Tree (Crescentia cujete L.) against Aeromonas hydrophilla: Natural drug use extracts of calabash tree to control the growth of Aeromonas hydrophilla by In vitro - Noorkomala Sari; Nengah Dwianita Kuswytasari; Awik Puji Dyah Nurhayati (Biota, 2020)
Study to determine the antibacterial activity of wet and dry extract of the leaf, fruit, and bark of Calabash tree (Crescentia cujete L.) against the growth of Aeromonas hydrophila. The solvent extraction process was done by using 96% ethanol in the maceration method. Antibacterial test results using diffusion agar to decide clear zone and tube series of dilution test to provide MIC and MBC. Fresh leaf extract produces the highest clear zone diameter (20.06 mm), after which fresh bark extract (12.81 mm), and the last is fresh fruit extract (3.22 mm). In contrast to fresh extracts, the dried extracts are have not clear zone. MIC (Minimum Inhibitory Concentration) of Calabash Tree fresh leaf extract against Aeromonas hydrophila is 80%, and MBC (Minimum Bactericidal Concentration) is 100%.